2013
DOI: 10.1590/s1413-81232013000400004
|View full text |Cite
|
Sign up to set email alerts
|

Panorama da compra de alimentos da agricultura familiar para o Programa Nacional de Alimentação Escolar

Abstract: This article seeks to describe the viewpoint of purchasing food products from family farmers, analyzing their performance within the new guidelines of the Brazilian School Nutrition Program (PNAE). It is a critical assessment based on a review of the literature and the official data provided by the National Fund for the Development of Education/Ministry of Education relating to 2010. The program budget in 2010 was approximately R$2.5 billion and attended 45.6 million children, adolescents and adults. From the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
1
144

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(210 citation statements)
references
References 3 publications
0
46
1
144
Order By: Relevance
“…In a previous study nationwide was identified that eight of the 18 cities analyzed also acquired over 30% of the resource (TOYOYOSHI et al, 2013). Considering only the Brazilian southeast region, the purchase over 30% was reported by 42.4% of cities (SARAIVA et al, 2013).…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…In a previous study nationwide was identified that eight of the 18 cities analyzed also acquired over 30% of the resource (TOYOYOSHI et al, 2013). Considering only the Brazilian southeast region, the purchase over 30% was reported by 42.4% of cities (SARAIVA et al, 2013).…”
Section: Resultsmentioning
confidence: 90%
“…In a nationwide study this same cause represented 21.1% of the justifications for not performing the purchase (SARAIVA et al, 2013). Other authors pointed out that the difficulty for the purchase, may be due to the presence of large companies of the sector involved in selling food to the government and public institutions (REAL & SCHNEIDER, 2013), as well as technological limitations and the reduced manpower in small properties (RIBEIRO et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dentre outros aspectos incorporados ao programa a partir de 2003, destacam-se a extensão de sua cobertura a escolas de populações diferenciadas, como indí-genas e quilombolas, com um valor per capita por aluno superior àquele destinado a alunos da sociedade envolvente 3 ; a obrigatoriedade de que as escolas indígenas e quilombolas forneçam, no mínimo, 30% das necessidades nutricionais diá-rias dos alunos por refeição e, quando em perío-do integral, no mínimo 70% 3 3 , as quais estipulam que, no mínimo, 30% do total dos recursos repassados do FNDE sejam destinados à compra de alimentos, preferencialmente orgânicos, produzidos pela agricultura familiar local, regional ou nacional 5 . Em relação a este último aspecto, o programa intenciona impactar na vocação agrí-cola dos municípios, fomentando o desenvolvimento da economia local, além do incentivo e respeito aos hábitos e alimentos regionais.…”
Section: Há Poucos Estudos Sobre O Programa Nacional De Alimentação Eunclassified